HUBUNGAN BERAT DERAJAT MEROKOK TERHADAP KELAINAN FUNGSI PARU PADA SOPIR ANGKUTAN UMUM DI TERMINAL KAMPUNG MELAYUJAKARTA TIMUR TAHUN 2023 - Rizaldi Ridwan, (2023)
In Indonesia, the prevalence of lung function disorders is 9.2 million. Public transport drivers who smoke have a risk of lung function abnormalities caused by smoking. This study aims to analyze the relationship between the weight of smoking degrees to symptoms of lung function abnormalities in public transport drivers at Kampung Melayu Terminal. This research was carried out in May 2023 at the Kampung Melayu Terminal using quantitative methods of cross-sectional research design with a total sample of 102. Sampling using purposive sampling techniques with inclusion criteria of public transport drivers smokers and willing to be interviewed. The instruments used are questionnaires and spirometry and use the cox regression test. Univariate results found that out of 102 respondents, there were 64.71% experiencing restriction and 6.86% experiencing obstruction and 47.06% having moderate smoking degree weight. The results of multivariate analysis using Cox Regression showed that the weight of smoking degrees in the moderate category (PR= 2.076; p-value 0.020; 95% CI 1.119-3.850) and in the weight category (PR=2.326; p-value 0.020; 95% CI 1.142-4.734) had a significant relationship with the risk of lung function abnormalities influenced by the covariate variable of knowledge the danger of smoking (1.358 times more risk of poor knowledge). The conclusion is that the degree of smoking weight has a relationship to the risk of lung function abnormalities once controlled with knowledge of the danger of smoking.